Asymmetric synthesis of primary amines catalyzed by thermotolerant fungal reductive aminases. Issue 19 (5th May 2020) - Mangas-Sanchez, Juan; Sharma, Mahima; Cosgrove, Sebastian C.; Ramsden, Jeremy I.; Marshall, James R.; Thorpe, Thomas W.; Palmer, Ryan B.; Grogan, Gideon; Turner, Nicholas J.
Abstract : Fungal reductive aminases as effective biocatalysts for the preparation of chiral primary amines. Abstract : Chiral primary amines are important intermediates in the synthesis of pharmaceutical compounds. Fungal reductive aminases (RedAms) are NADPH-dependent dehydrogenases that catalyse reductive amination of a range of ketones with short-chain primary amines supplied in an equimolar ratio to give corresponding secondary amines. Herein we describe structural and biochemical characterisation as well as synthetic applications of two RedAms from Neosartorya spp. ( Nf RedAm and Nfis RedAm) that display a distinctive activity amongst fungal RedAms, namely a superior ability to use ammonia as the amine partner. Using these enzymes, we demonstrate the synthesis of a broad range of primary amines, with conversions up to >97% and excellent enantiomeric excess. Temperature dependent studies showed that these homologues also possess greater thermal stability compared to other enzymes within this family. Their synthetic applicability is further demonstrated by the production of several primary and secondary amines with turnover numbers (TN) up to 14 000 as well as continous flow reactions, obtaining chiral amines such as ( R )-2-aminohexane in space time yields up to 8.1 g L −1 h −1 . The remarkable features of Nf RedAm and Nfis RedAm highlight their potential for wider synthetic application as well as expanding the biocatalytic toolbox available for chiral amine synthesis.